Pengembangan Bahan Ajar Berorientasi Kontekstual dalam Pembelajaran IPAS Materi Seperti Apakah Budaya Daerahku di Kelas V SDN 24 Pontianak Tenggara - Lia Uladari; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Journal on Education, 2024)
This research aims to produce contextually oriented teaching materials in IPAS learning. What is the culture of my region like in class V at SDN 24 Southeast Pontianak That is valid and practical to use. The research method used is research and development (Research & Development) by adapting the ADDIE model. The data sources for this research are the results of the validation of two expert validators and student response questionnaires. The research instruments are interviews and questionnaires. The results of research on the development of Contextually Oriented Teaching Materials based on needs analysis are the need for teaching materials with the characteristics of attractive teaching materials in terms of design, material related to real life, interesting supporting images related to the material, exercises in the form of activities carried out in groups and questions. At the end of the lesson, the level of feasibility of the teaching material design as assessed by the Hali validator was declared "Valid", while the level of feasibility of the contextually oriented teaching material product in the material aspect received a score with an average of 4.67 in the "Very Valid" category, the language aspect received a score with an average of 4.5 in the "Very Valid" category, and the design aspect received a score of 4.61 in the "Very Valid" category. The level of practicality of the teaching materials obtained from the small group student response questionnaire was 4.58 in the "Very Practical" category and the large group obtained an average score of 4.69 in the "Very Practical" category.